More than a feeling: A global economic valuation of subjective wellbeing damages resulting from rising temperatures. - Stephan Dietrich; Stafford Nichols (PLoS ONE)
When estimating economic and welfare effects from climate change, impact models must make broad assumptions because of a lack of data and the complexity of damage mechanisms. In this paper, we apply a novel approach to try and address this issue. We use an experienced utility approach to measure how extreme heat affects subjective wellbeing. The data comes from a life evaluation question collected on nationally representative surveys covering 160 countries, conducted annually for 13 years. We take advantage of 40 years of variation in daily land surface temperature data, finding that one additional exceptionally hot day significantly lowers wellbeing, by roughly 0.5% on average. This is equivalent to the wellbeing loss resulting from GDP decreasing by several percentage points. The effect size varies substantially between, and within, countries, highlighting the importance of having local data. Further, we analyze the source of wellbeing damages, by looking at income and non-income pathways. Suprisingly, we find that income pathways accounts for only a small proportion of wellbeing damages caused by extreme temperatures. This indicates current models that focus on income pathways are likely missing sources of climate-caused damages.